Company–Community Agreements, Gender and Development - Keenan, J. C. (Journal of business ethics, 2016)
Company–community agreements are widely considered to be a practical mechanism for recognising the rights, needs and priorities of peoples impacted by mining, for managing impacts and ensuring that mining-derived benefits are shared. The use and application of company–community agreements is increasing globally. Notwithstanding the utility of these agreements, the gender dimensions of agreement processes in mining have rarely been studied. Prior research on women and mining demonstrates that women are often more adversely impacted by mining than men, and face greater challenges in accessing development opportunities that mining can bring. Nonetheless, there is currently little guidance for companies, government or communities in bringing a gender perspective to the fore in mining and agreement processes. It is undisputed in human development literature that investment in women and sensitivity to gender delivers long-term health, education and local development outcomes. In mining and development, a number of key factors remain unexplored. These include: women’s participation in agreement processes, the gendered distribution of agreement benefits, and the extent to which impacts and benefits influence women’s development and economic inclusion. This paper presents the results of the first phase of an applied research project undertaken by the Centre for Social Responsibility in Mining (CSRM) at The University of Queensland and funded by the Minerals Council of Australia (MCA) and the Department of Foreign Affairs and Trade (DFAT). The project sought to connect with experienced practitioners who had been directly involved in mining and agreement processes to document and analyse grounded perspectives on gender dynamics and agreements, and connect those experiences with the broader literature. Findings from this study have implications for the role of mining companies and governments in promoting gender equality and empowerment as part of their commitments to sustainable development. They also have implications for community groups and their representatives in terms of how they might engage in agreement processes to maximise women’s participation and influence. In many social contexts, a key challenge will be navigating the territory of cultural norms and gender equality, particularly in cultures where women’s influence in the public sphere is not strong. The authors argue that without consideration of a gender perspective, including gender’s intersection with other factors such as class, race, poverty level, ethnic group and age, mining agreements will not be inclusive, may exacerbate gender inequalities, and fail to contribute to long-term sustainable development.